1999
DOI: 10.5511/plantbiotechnology.16.389
|View full text |Cite
|
Sign up to set email alerts
|

Identification and cDNA cloning for S-RNases in self-incompatible Japanese plum (Prunus salicina Lindl. cv. Sordum).

Abstract: This report demonstrates the presence of S-RNases in style of self-incompatible Japanese plum (Prunus salicina Lindl.) and presents information about cDNA sequencese ncoding the S-RNases. Two stylar glycoprotein spots that were found in highly basic zone of 2D-PAGE gel with Mr of about 30 kDa shared similarity in N-terminal amino acid sequence and immunological characteristics with other rosaceous S-RNases and appeared to be S-RNases of Japanese plum. Deduced amino acid sequences from the cDNA clones encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Because of the presence of at least two multi-allelic genes, the term "haplotype" has been used to describe variants of the S-locus and the term "allele" to describe variants of a given polymorphic gene at the S-locus (McCubbin and Kao 2000). In the Solanaceae and the Rosaceae, the gene controlling the pistil's SI response is a ribonuclease (S-RNase) which is expressed only in the pistil (McClure et al 1989;Sassa et al 1992;Lee et al 1994;Murfett et al 1994;Broothaerts et al 1995;Boškovic and Tobutt 1996;Ishimizu et al 1996;Sassa et al 1996;Tomimoto et al 1996;Tao et al 1997Tao et al , 1999Burgos et al 1998;Ushijima et al 1998;Yamane et al 1999). A second gene that is hypothesized to be expressed specifically in the pollen has yet to be determined from any GSI species.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the presence of at least two multi-allelic genes, the term "haplotype" has been used to describe variants of the S-locus and the term "allele" to describe variants of a given polymorphic gene at the S-locus (McCubbin and Kao 2000). In the Solanaceae and the Rosaceae, the gene controlling the pistil's SI response is a ribonuclease (S-RNase) which is expressed only in the pistil (McClure et al 1989;Sassa et al 1992;Lee et al 1994;Murfett et al 1994;Broothaerts et al 1995;Boškovic and Tobutt 1996;Ishimizu et al 1996;Sassa et al 1996;Tomimoto et al 1996;Tao et al 1997Tao et al , 1999Burgos et al 1998;Ushijima et al 1998;Yamane et al 1999). A second gene that is hypothesized to be expressed specifically in the pollen has yet to be determined from any GSI species.…”
Section: Introductionmentioning
confidence: 99%
“…is a commercially important fruit crop, which exhibits GSI. Yamane et al (1999) have demonstrated the presence of S-RNases in Japanese plum and have cloned two of their cDNAs. S-RNase in Japanese plum is a basic glycoprotein with Mr of about 30 kDa containing two active sites for T2/S type RNases, five conserved regions and one hypervariable region and is expressed exclusively in the pistil.…”
Section: Introductionmentioning
confidence: 99%
“…et Zucc.) that belongs to the Rosaceae exhibits S-RNase-based gametophytic self-incompatibility Yaegaki et al 2001), as do most other Prunus fruit tree species (Tao et al 1997Ushijima et al 1998;Yamane et al 1999Yamane et al , 2001. Although both self-incompatible and selfcompatible cultivars are grown commercially in Japan, self-compatible cultivars have a horticultural advantage over self-incompatible cultivars because no cross-pollinizer is required.…”
Section: Introductionmentioning
confidence: 99%